Managerialism and teacher professional identity: impact on well-being among teachers in the UK. Issue 1 (2nd January 2021) - Skinner, Barbara; Leavey, Gerard; Rothi, Despina
ABSTRACT: In Europe, well-being in the workplace has increasing prominence in the policy and research agenda, and education is a key context in which the challenge of occupational stress has been reported. Traditionally, the ethos in school settings could be said to be shaped by the vocational motivation of employees; that is, a commitment to a social benefit through the development, support and improvement of the pupils, and this commitment used to override workplace challenges and help teachers deal with stress. This article argues that teachers' commitment is being eroded by the impact of bureaucratic changes at management level, such as the setting of performance targets, increased workload, increased accountability and changes in the curriculum. This in turn impacts on their professional identity and can negatively affect their mental health and well-being. The current article describes a qualitative study undertaken among 39 teachers and 6 school leaders across England and Wales in which we sought to understand, through interviews, the contextual workplace experiences of teachers who experienced work-related stress. Policy developments in education and management implementation of these developments and the consequent erosion of teacher autonomy dominated the narratives. We examine how managerialism can relate to a loss of commitment, professional identity, self-confidence and vulnerability to stress, anxiety and depression. This article proposes that educational reforms, and the rigidly prescribed organisational and management structures that accompany them, need to be weighed against their impacts on professional identity and personal well-being.